Influence of different central nozzle diameters and powder injection rates on carbon powder mixed injection with shrouding supersonic oxygen jet (CMISSO) lance. (14th September 2022) - Tian, Bohan; Wei, Guangsheng; Zhu, Rong; Li, Xin; Zhang, Hongjin
ABSTRACT: In order to improve the carbon powder utilization efficiency in electric arc furnace (EAF) steelmaking process, the carbon powder mixed injection with shrouding supersonic oxygen jet (CMISSO) lance was designed. In this study, the effects of different central nozzle diameters and powder injection rates on the dynamic characteristics of CMISSO lance are studied by numerical simulation, and the reliability of numerical simulation is verified by cold test. The results show that when the diameter of the central nozzle is 10, 15 and 20 mm, the mixing distance is 0.18, 0.28 and 0.30 m. Depicting that 10 mm centre nozzle diameter is the easiest to merge the central jet and the shrouding jet. The application of CMISSO injection lance can effectively make the powder get together. In addition, the larger the powder flow, the larger the powder distribution range and the lower the utilization efficiency.